Limosilactobacillus reuteri Strains as Adjuvants in the Management of Helicobacter pylori Infection - Dargenio, Costantino (Medicina (Kaunas), 2021)
Helicobacter pylori (HP) is a Gram-negative bacterium which finds its suitable habitat in the stomach. The infection affects about half of the global population with high variability in prevalence among regions and for age. HP is the main causative agent of chronic active gastritis, peptic and duodenal ulcers, and may be the primary cause of gastric cancer or MALT lymphoma. Due to the high rate of failure of eradication therapy in various countries and the increase in antibiotic resistance reported in the literature, there is an ever wider need to seek alternative therapeutic treatments. Probiotics seem to be a promising solution. In particular, the Limosilactobacillus reuteri (L. reuteri) species is a Gram-positive bacterium and is commonly found in the microbiota of mammals. L. reuteri is able to survive the gastric acid environment and bile and to colonize the gastric mucosa. This species is able to inhibit the growth of several pathogenic bacteria through different mechanisms, keeping the homeostasis of the microbiota. In particular, it is able to secrete reuterin and reutericycline, substances that exhibit antimicrobial properties, among other molecules. Through the secretion of these and the formation of the biofilm, it has been found to strongly inhibit the growth of HP and, at higher concentrations, to kill it. Moreover, it reduces the expression of HP virulence factors. In clinical trials, L. reuteri has been shown to decrease HP load when used as a single treatment, but has not achieved statistical significance in curing infected patients. As an adjuvant of standard regimens with antibiotics and pump inhibitors, L. reuteri can be used not only to improve cure rates, but especially to decrease gastrointestinal symptoms, which are a common cause of lack of compliance and interruption of therapy, leading to new antibiotic resistance.